Protective Efficacy and Safety of Three Antimalarial Regimens for the Prevention of Malaria in Young Ugandan Children: A Randomized Controlled Trial doi:10.1371/journal.pmed.1001689 - Bigira, Victor; Kapisi, James; Clark, Tamara D.; Kinara, Stephen; Mwangwa, Stephen; Muhindo, Mary K.; Osterbauer, Beth; Aweeka, Francesca T.; Huang, Liusheng; Achan, Jane; Havlir, Diane V.; Rosenthal, Philip J.; et al. (PLoS medicine, 2014)
Chemoprevention offers a promising strategy for prevention of malaria in African children. However, the optimal chemoprevention drug and dosing strategy is unclear in areas of year-round transmission and resistance to many antimalarial drugs. To compare three available regimens, we conducted an open-label randomized controlled trial of chemoprevention in Ugandan children. Methods and Findings: This study was conducted between June 28, 2010, and September 25, 2013. 400 infants were enrolled and 393 randomized at 6 mo of age to no chemoprevention, monthly sulfadoxine-pyrimethamine (SP), daily trimethoprim-sulfamethoxazole (TS), or monthly dihydroartemisinin-piperaquine (DP). Study drugs were administered at home without supervision. Piperaquine (PQ) levels were used as a measure of compliance in the DP arm. Participants were given insecticide-treated bednets, and caregivers were encouraged to bring their child to a study clinic whenever they were Chemoprevention was stopped at 24 mo of age, and participants followed-up an additional year. Primary outcome was the incidence of malaria during the intervention period. During the intervention, the incidence of malaria in the no chemoprevention arm was 6.95 episodes per person-year at risk. Protective efficacy was 58% (95% CI, 45%–67%, p,0.001) for DP, 28% (95% CI, 7%–44%, p = 0.01) for TS, and 7% for SP (95% CI, 219% to 28%, p = 0.57). PQ levels were below the detection limit 52% of the time when malaria was diagnosed in the DP arm, suggesting non-adherence. There were no differences between the study arms in the incidence of serious adverse events during the intervention and the incidence of malaria during the 1-y period after the intervention was stopped.Conclusions: For preventing malaria in children living in an area of high transmission intensity, monthly DP was the mostefficacious and safe, although adherence may pose a problem.Monthly SP and daily TS may not be appropriate in areas with high transmission intensity and frequent resistance to antifolates.
Keywords: Antimalarial Regimens; Prevention; Malaria; Young Children